Endometrial adenocarcinoma occuring in young women - Kubelka-Sabit, Katerina; Prodanova, Irina; Yashar, Genghis; Zografski, George; Basheska, Neli (Hellenic Division of International Academy of Pathology, 2003)
Background: Endometrial adenocarcinoma (EA) primarily occurs in postmenopausal women. Only 1-8% of the cases are diagnosed in women under forty years of age, while this neoplasm is extremely rare in the third decade. Hysterectomy with bilateral salpingo-oophorectomy and pelvic lymphadenectomy (HSOPL) is the treatment of choice for older or patients with invasive EA. However, in young women with non-invasive well-differentiated EAs, who wish to preserve their fertility, conservative treatment with progestins can be tried. Aims: The purpose of this retrospective study is to present the clinical and morphologic characteristics, as well as the immunohistochemical profile of 3 cases of well-differentiated EAs, that occurred in women in their third decade of life. Since the neoplasms were non-invasive, an attempt to preserve their fertility has been made. Methods and patients: Six of the 1081 cases (0.5%) of EA diagnosed at the Department of Histopathology and Clinical Cytology in the last 14-year period (1989-2002), occurred in patients younger than 35 years. Three of them (1.4%, 3/206), have been diagnosed in the last two years (2001-2002). The youngest of the last three patients (age 21), had a genetic abnormality (45X/47XXX) and experienced prolonged and heavy uterine bleedings that required explorative curettage. The second patient (age 25) had a history of diabetes and infertility. The neoplasm was found in the endometrial biopsy that was taken for evaluation of the endometrial response to hormonal stimulation. In the third patient (age 27) the neoplasm was an accidental finding in the cervical curettage material that was submitted to our department, for histopathologic reevaluation of the previously diagnosed moderate dysplasia of the epithelium of the uterine cervix. The materials, obtained either by dilatation and curettage (3 cases) or HSOPL (one case), were submitted to our department and were routinely processed. Standard hematoxylin and eosin (H&E) stained slides were prepared from paraffin blocks, whereas additional histochemical (PAS, alcian blue, azan, silver by Jones) and immunohistochemical stains (estrogen-ER, progesterone-PgR, p53, Ki-67) were performed on selected paraffin blocks that contained the neoplastic tissue. Results: In the curettage materials of the three patients, fragments of endometrial polyp were identfied, that contained areas of simple, complex and atypical hyperplasia. In each of these cases, only few small (1-3-millimetre in diameter) foci of well-differentiated EA were detected. Fragments of functional endometrium were also present. All three patients had hormone (ER, PgR) responsive neoplasms, whereas Ki-67 proliferative index was significantly higher in the neoplastic tissue (30-40%), compared to the zones of atypical hyperplasia (10-20%). The suppressor gene protein product p53 was negative in all three EAs. Subsequent dilatation and curettage to remove the residual parts of the polyp was performed in two of the patients. Conservative 5-6-month treatment with progestins led to regression of the disease in all patients, documented by endoscopy and curettage in two patients. As for the youngest patient, clinical decision for HSOPL has been made, and multiple sections of the operative material did not show any residual EA. Conclusions: Even though extremely rare, EAS may occur in asymptomatic patient and/or in young women without clinical evidence of polycystic ovary disease. In these patients careful histopathologic evaluation of the curettage material is essential, in order to select the ones to whom conservative fertility-preserving treatment can be offered.
Abstracts of the Intraeuropean Mediterranean Conference of the International Academy of Pathology, May 8-10, 2003, Athens, Greece: Hellenic Division of IAP; 2003:86
Keywords: endometrium; adeocarcinoma; young women; fertility preservation; histopathology; immunohistochemistry; conservative treatment